Knowledge and Attitude of Nigerian Women Aged 15-49 Years on the Practice of Female Genital Mutilation - Chidimma Ezenwa Anyanwu; Kwasi Torpey; Olaniyi Sanni; Olaiya Paul Abiodun; Ifeanyi Donald Anyanwu (Journal of Epidemiology and Public Health, 2025)
Background: Female genital mutilation (FGM) is among the most harmful traditions that persist in many parts of the world, especially in Africa and other developing countries, including Nigeria, where the prevalence of FGM is still above 15%. This study aims to assess the knowledge and attitude of Nigerian women of reproductive age on FGM practice and its obstetric effects.Subjects and Method: This cross-sectional study examined Abujaarea women aged 15–49 in Nyanya General Hospital, Maitama, and Asokoro District Hospital Antenatal Care (ANC). A total of 634 patients who agreed to participate in the study were selected. The assessment examined respondents' knowledge and opinions about Female Genital Mutilation (FGM), sources of information, attitudes and beliefs, prevalence across three generations, and recommendations. Data was collected using Google Forms, and various statistical tests were analyzed using IBM SPSS version 25.Results: This study comprised 634 females, the majority of whom had post-secondary education (62.6%) and were married (96.8%), of which 29.2% were within the age group 30–34. Most of the respondents (86.3%) had previously heard about FGM. Of those interviewed, 49.5% knew FGM was practiced in their community, and 326 (51.4%) affirmed knowledge of health problems associated with FGM. The Major source of information on FGM was from parents (36.1%), followed by the media (26.1%). Two hundred and thirty-two respondents (36.6%) strongly agreed that FGM is a very harmful and inhumane practice, and a majority (91.8%) had no intention to circumcise their daughters. About 56.0% strongly agreed and recommended a campaign against FGM in school, and 53.8% strongly agreed to educate traditional birth attendants on the risk of FGM.Conclusion: This study found that the respondents had good knowledge of FGM and its obstetric effects. However, most respondents had a negative attitude towards FGM. Hence, a need for more innovative interventions towards its eradication.